EFEKTIFITAS PENERAPAN E-MODUL BERBASIS PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN PROSES SAINS SISWA SMA - Sri Mayanty; I Made Astra; Cecep E. Rustana (Navigation Physics : Journal of Physics Education, 2020)
This study aims to improve science process skills of class X1 high school students in private school in Tasikmalaya regency through the application of problem based learning (PBL) based e-modules. Data on studnets’ process skills ability were obtained through quantitave data. The research design used was true experimental research with a pretest-posttest control group design. Quantitave data were obtainedd through the pretest and posttest which included tests of scientific processing skills (cognitive). The result of the effectiveness test illustrate that the e-module based on Problem Based Learning can improve students’ science process skils with a gain score for the control and treatment groups obtained tcount = 2,576 > ttabel = 2,002 at α = 0,05. Although the effective contribution of treatment to the treatment class was only approximately 10,6%, the effectiveness of this e-module is supported by presentasion of problem based material which is able to encourage students to learn.